Polyclonal Tumors in the Mammalian Intestine: Are interactions among multiple initiated clones necessary for tumor initiation, growth, and progression? - Halberg, Richard B. (2007)
Studies in both man and mouse indicate that the majority of familial intestinal tumors are polyclonal being composed of cells from at least two distinct progenitors. The formation of polyclonal tumors in the mouse can be explained by short-range interactions between multiple initiated clones within one or two crypt diameters of each other. These clonal interactions might be critical, if not necessary, for initiation, growth, progression, or all three stages of tumorigenesis. This view is diametrically opposed to the widely held view that intestinal tumors are monoclonal and progress by clonal expansion. The data supporting the latter are neither extensive nor definitive. In addition, the results from a recent study indicate that earlier studies of tumor clonality were heavily biased because lineage patches in the intestinal epithelium of humans resulting from X-inactivation are relatively large. Consequently, hundreds of tumors from familial and sporadic cases need to be analyzed to accurately assess tumor clonality. Investigators must keep an open mind regarding the clonality of tumors in the mammalian intestine as new experimental approaches are developed which will eventually provide a definitive answer to this fundamental question in the field of cancer biology.